Sarcolemmal Excitability, M-Wave Changes, and Conduction Velocity During a Sustained Low-Force Contraction - Rodriguez-Falces, Javier; Place, Nicolas (Frontiers in Physiology, 2021)
This study was undertaken to investigate whether sarcolemmal excitability is impaired during a sustained low-force contraction (10% MVC) by assessing muscle conduction velocity and also by analyzing separately the first and second phases of the muscle compound action potential (M wave). Twenty one participants sustained an isometric knee extension of 10% MVC for 3 min. M waves were evoked by supramaximal single shocks to the femoral nerve given at 10-s intervals. The amplitude, duration, and area of the first and second M-wave phases were computed. Muscle fiber conduction velocity, voluntary surface EMG, perceived effort, MVC force, peak twitch force and temperature were also recorded. The main findings were: (1) During the sustained contraction, conduction velocity remained unchanged. (2) The amplitude of the M-wave first phase decreased for the first ~30s (-7%, P<0.05), and stabilized thereafter, whereas the second phase amplitude increased for the initial ~30s (+7%, P<0.05), before stabilizing; (3) Both duration and area decreased steeply during the first ~30s, and then more gradually for the rest of the contraction; (4) During the sustained contraction, perceived effort increased fivefold, whereas knee extension EMG increased by ~10%; (5) Maximal voluntary force and peak twitch force decreased (respectively, -9% and -10%, P<0.05) after the low-force contraction. Collectively, the present results indicate that sarcolemmal excitability is well preserved during a sustained 10% MVC task. A depression of the M-wave first phase during a low-force contraction can occur even in the absence of changes in membrane excitability. Development of fatigue during a low-force contraction can occur without alteration of membrane excitability.